Fibroblast growth factors in control of lipid metabolism: from biological function to clinical application. Issue 3 (June 2019) - Struik, Dicky; Dommerholt, Marleen B.; Jonker, Johan W.
Abstract : Purpose of review: Several members of the fibroblast growth factor (FGF) family have been identified as key regulators of energy metabolism in rodents and nonhuman primates. Translational studies show that their metabolic actions are largely conserved in humans, which led to the development of various FGF-based drugs, including FGF21-mimetics LY2405319, PF-05231023, and pegbelfermin, and the FGF19-mimetic NGM282. Recently, a number of clinical trials have been published that examined the safety and efficacy of these novel therapeutic proteins in the treatment of obesity, type 2 diabetes (T2D), nonalcoholic steatohepatitis (NASH), and cholestatic liver disease. In this review, we discuss the current understanding of FGFs in metabolic regulation and their clinical potential. Recent findings: FGF21-based drugs induce weight loss and improve dyslipidemia in patients with obesity and T2D, and reduce steatosis in patients with NASH. FGF19-based drugs reduce steatosis in patients with NASH, and ameliorate bile acid-induced liver damage in patients with cholestasis. In contrast to their potent antidiabetic effects in rodents and nonhuman primates, FGF-based drugs do not appear to improve glycemia in humans. In addition, various safety concerns, including elevation of low-density lipoprotein cholesterol, modulation of bone homeostasis, and increased blood pressure, have been reported as well. Summary: Clinical trials with FGF-based drugs report beneficial effects in lipid and bile acid metabolism, with clinical improvements in dyslipidemia, steatosis, weight loss, and liver damage. In contrast, glucose-lowering effects, as observed in preclinical models, are currently lacking.